Changes in anxiety and depression during the COVID-19 pandemic in the European population: A meta-analysis of changes and associations with restriction policies - Veeleah Lok; Hugo Sjöqvist; Anna Sidorchuk; Pär Flodin; Walter Osika; Michael Daly; Philip Hyland; Lars H. Andersen; Peter Fallesen; Marcelo C. Cabrera; Ann K.S. Knudsen; Karen Wetherall; et al. (European Psychiatry, 2023)
Abstract